2016
DOI: 10.1071/mf15158
|View full text |Cite
|
Sign up to set email alerts
|

Age- and sex-dependent changes in morphometric and metabolic variables in the long-lived freshwater mussel Diplodon chilensis

Abstract: Markers of oxidative stress and biochemical composition were investigated in digestive gland and gonad tissues in the freshwater mussel Diplodon chilensis, as well as morphometric variables in relation to chronological age and sex. Individual growth followed a von Bertalanffy growth model (VBGM). Superoxide dismutase activity, glutathione level and oxidative damage to proteins remain constant through the life of both tissues, whereas catalase and glutathione-Stransferase activities and lipid peroxidation decre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 53 publications
(57 reference statements)
0
6
0
Order By: Relevance
“…Furthermore, specific features of the naiad’s life cycle need to be considered [ 24 ], [ 25 ]. For example, some life cycles include a parasitic phase, some are very long-lived (certain European species live as long as 200 years) [ 48 ] and some individuals that reach maturity are potentially resistant to certain environmental changes, enabling them to survive for a long time [ 38 ], [ 39 ]. This particular life history is not necessarily shortened by environmental alterations such as the construction of dams and reservoirs [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, specific features of the naiad’s life cycle need to be considered [ 24 ], [ 25 ]. For example, some life cycles include a parasitic phase, some are very long-lived (certain European species live as long as 200 years) [ 48 ] and some individuals that reach maturity are potentially resistant to certain environmental changes, enabling them to survive for a long time [ 38 ], [ 39 ]. This particular life history is not necessarily shortened by environmental alterations such as the construction of dams and reservoirs [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although taxonomical and biological studies of Unionida in Argentina increased during the 1960s and 70s [ 6 ], [ 12 ], [ 14 ], [ 15 ], [ 17 ], [ 18 ], [ 34 ], [ 35 ], [ 36 ], [ 37 ] they were discontinued in the late twentieth and early twenty-first centuries, leading to deficient knowledge on current populations. The species Diplodon ( Diplodon ) chilensis (Gray, 1828) is an exception, as research has been conducted into the physiology and toxicology of its populations in Patagonia [ 38 ], [ 39 ].…”
Section: Introductionmentioning
confidence: 99%
“…Lipid peroxidation levels were estimated by spectrophotometric quantification at 535 nm (UV-160A, Shimadzu) of thiobarbituric acid reactive substances (TBARS) according to Buege and Aust (1978) (modified, Yusseppone et al, 2015). Data were expressed as nmol TBARS g −1 WM.…”
Section: Oxidative Damagementioning
confidence: 99%
“…More recently, Bianchi and colaborators (Bianchi, Castro, Rocchetta, Bieczynski, & Luquet, ; Bianchi, Rocchetta, & Luquet, ; Bianchi et al, ) have shown that immune response biomarkers of this species are suitable for detecting domiciliary waste water contamination. Due to its abundance and longevity, which can exceed a century (Rocchetta, Lomovasky, et al, ; Soldati, Jacob, Schone, Bianchi, & Hajduk, ; Yusseppone, Lomovasky, Luquet, Ríos de Molina, & Rocchetta, ), D. chilensis has been proposed as a sentinel species for long‐term monitoring of the environmental health of Patagonian freshwater bodies. A recent decline in D. chilensis river populations has been reported in Chile as a consequence of habitat deterioration (Parada & Peredo, ; Parada, Peredo‐Parada, Quevedo, & Peredo, ), but there are no reports on water quality deterioration in Argentinean rivers populated by this species (Yusseppone et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…More recently, Bianchi and colaborators (Bianchi, Castro, Rocchetta, Bieczynski, & Luquet, 2014;Bianchi et al, 2015) have shown that immune response biomarkers of this species are suitable for detecting domiciliary waste water contamination. Due to its abundance and longevity, which can exceed a century (Rocchetta, Lomovasky, et al, 2014;Soldati, Jacob, Schone, Bianchi, & Hajduk, 2009;Yusseppone, Lomovasky, Luquet, Ríos de Molina, & Rocchetta, 2015), D. chilensis has been proposed as a sentinel species for long-term monitoring of the environmental health of Patagonian freshwater bodies. A recent decline in D.…”
mentioning
confidence: 99%